The Southern Ocean during the ice ages: A review of the Antarctic surface isolation hypothesis, with comparison to the North Pacific. (15th February 2021) - Sigman, Daniel M.; Fripiat, François; Studer, Anja S.; Kemeny, Preston C.; Martínez-García, Alfredo; Hain, Mathis P.; Ai, Xuyuan; Wang, Xingchen; Ren, Haojia; Haug, Gerald H.
Abstract: The Southern Ocean is widely recognized as a potential cause of the lower atmospheric concentration of CO2 during ice ages, but the mechanism is debated. Focusing on the Southern Ocean surface, we review biogeochemical paleoproxy data and carbon cycle concepts that together favor the view that both the Antarctic and Subantarctic Zones (AZ and SAZ) of the Southern Ocean played roles in lowering ice age CO2 levels. In the SAZ, the data indicate dust-driven iron fertilization of phytoplankton growth during peak ice age conditions. In the ice age AZ, the area-normalized exchange of water between the surface and subsurface appears to have been reduced, a state that we summarize as "isolation" of the AZ surface. Under most scenarios, this change would have stemmed the leak of biologically stored CO2 that occurs in the AZ today. SAZ iron fertilization during the last ice age fits with our understanding of ocean processes as gleaned from modern field studies and experiments; indeed, this hypothesis was proposed prior to evidentiary support. In contrast, AZ surface isolation is neither intuitive nor spontaneously generated in climate model simulations of the last ice age. In a more prospective component of this review, the suggested causes for AZ surface isolation are considered in light of the subarctic North Pacific (SNP), where the paleoproxies of productivity and nutrient consumption indicate similar upper ocean biogeochemical changes over glacial cycles, although with different timings at deglaciation. Among the proposed initiators of glacial AZ surface isolation, a single mechanism is sought that can explain the changes in both the AZ and the SNP. The analysis favors a weakening and/or equatorward shift in the upwelling associated with the westerly winds, occurring in both hemispheres. This view is controversial, especially for the SNP, where there is evidence of enhanced upper water column ventilation during the last ice age. We offer an interpretation that may explain key aspects of the AZ and SNP observations. In both regions, with a weakening in westerly wind-driven upwelling, nutrients may have been "mined out" of the upper water column, possibly accompanied by a poleward "slumping" of isopycnals. In the AZ, this would have encouraged declines in both the nutrient content and the formation rate of new deep water, each of which would have contributed to the lowering of atmospheric CO2 . Through several effects, the reduction in AZ upwelling may have invigorated the upwelling of deep water into the low latitude pycnocline, roughly maintaining the pycnocline's supply of water and nutrients so as to (1) support the high productivity of the glacial SAZ and (2) balance the removal of water from the pycnocline by the formation of Glacial North Atlantic Intermediate Water. The proposed return route from the deep ocean to the surface resembles that of Broecker's (1991) "global ocean conveyor, " but applying to the ice age as opposed to the modern ocean. Highlights: Southern Ocean processes lowered atmospheric CO2 concentrations during the ice ages. The Subantarctic Zone was fertilized with iron by increased dust supply. In the Antarctic Zone, the surface/deep exchange of water was reduced ("isolation"). The subarctic North Pacific Ocean may have undergone similar changes as the Antarctic Zone. Reduced westerly wind-driven upwelling may explain the "isolation" phenomenon.